2008
DOI: 10.1375/twin.11.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Adiponectin, Leptin, and BMI Among Adolescents in Taiwan: A Multivariate Twin/Sibling Analysis

Abstract: C irculating levels of leptin and adiponectin are closely associated with obesity. However, it is not known whether there are common shared genes or environment exerting influences on the levels of leptin, adiponectin, and BMI. We aimed to assess the relative contribution of genes and environment to adiponectin, leptin, and BMI individually as well as simultaneously to the three measures. Our subjects included a total of 228 twin/sibling pairs aged 12 to 18 (130 monozygotic twins, 68 dizygotic twins and 30 sib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
2
13
0
1
Order By: Relevance
“…Several studies have revealed a moderate to high estimate of heritability (30–70%) for plasma adiponectin levels, which are influenced by the interplay of several genes [27-30]. A meta-analysis of genome-wide association studies performed in nearly 40000 individuals in order to identify genes associated with adiponectin levels, revealed 8 loci and confirmed other 2 previously reported loci [31].…”
Section: Introductionsupporting
confidence: 66%
“…Several studies have revealed a moderate to high estimate of heritability (30–70%) for plasma adiponectin levels, which are influenced by the interplay of several genes [27-30]. A meta-analysis of genome-wide association studies performed in nearly 40000 individuals in order to identify genes associated with adiponectin levels, revealed 8 loci and confirmed other 2 previously reported loci [31].…”
Section: Introductionsupporting
confidence: 66%
“…A total of 88 independent estimates of BMI heritability from twin studies were identified from 31 papers (Stunkard et al, 1986, 1990; Hewitt et al, 1991; Korkeila et al, 1991; Neale and Cardon, 1992; Carmichael and McGue, 1995; Forbes et al, 1995; Harris et al, 1995; Herskind et al, 1996; Austin et al, 1997; Faith et al, 1999; Knoblauch et al, 1999; Narkiewicz et al, 1999; Pietilainen et al, 1999; Vinck et al, 1999; Baird et al, 2001; Poulsen et al, 2001; Schousboe et al, 2003, 2004; Nelson et al, 2006; Cornes et al, 2007; Hur, 2007; Ordonana et al, 2007; Silventoinen et al, 2007a,b; Souren et al, 2007; Hur et al, 2008; Liu et al, 2008; Wardle et al, 2008; Lajunen et al, 2009; Watson et al, 2010; Table 1; Figure A2 in Appendix). Reported estimates ranged from 0.47 to 0.90 (5th/50th/95th centiles: 0.58/0.75/0.87; Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found three twin studies that had pooled information on children at different ages. [27][28][29] We did not limit our search to weight, but except one early twin study, 27 all of these studies had used BMI or relative weight as an indicator of obesity. Two twin studies represented Korean population, 16,19 one Taiwanese population 29 and one had pooled information from four East Asian populations, 30 but otherwise the studies were conducted in the Caucasian populations.…”
Section: Search Strategymentioning
confidence: 99%